The Influence of Entrepreneurship Education, Self-Efficacy, and Locus of Control on College Student Entrepreneurial Interest in Elementary School Teacher Education - Khabibah, Febriyanti Ummi; Sani, Fakhrul; Nurjanah, Amanda Putri; Salimi, Moh (Social, Humanities, and Educational Studies (SHEs): Conference Series, 2019)
Entrepreneurship education as a method that is considered appropriate to minimize unemployment, but it is not easy to foster entrepreneurial interest for those subjects. This study aims to examine the effect of entrepreneurship education, self-efficacy and locus of control on entrepreneurship interests of elementary school teacher education students. This type of research is quantitative using a survey method through a questionnaire given to students. This study uses a validity test technique associated with product moment and reliability testing using Alpha Cronbanch. Based on the results of the study indicate that entrepreneurship education, self-efficacy and locus of control have a positive effect on student entrepreneurial interest